2022
DOI: 10.1038/s41598-022-27105-x
|View full text |Cite
|
Sign up to set email alerts
|

A case study on the bearing characteristics of a bottom uplift pile in a layered foundation

Abstract: The bottom uplift pile, which has been applied in practical projects, has the following advantages: the pile body is not easy to crack, good bearing characteristics, and small displacement of the pile top. Based on the bearing capacity test of foundation piles in the third stage expansion project of Lanzhou Zhongchuan International Airport, the upper part pile of the self-balancing test method was used to simulate the bottom uplift pile, and the anchor piles in the anchor pile method were regarded as normal up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…The test results led them to propose the utilization of a coefficient to evaluate the influence of pile installation methods on the pile's bearing capacity. He et al [17] compared the load-carrying capacity of bottom-uplift piles and anchor piles in their study, based on load tests on foundation piles. They found that bottom-uplift piles had double the peak load-carrying capacity of conventional uplift piles.…”
Section: Introductionmentioning
confidence: 99%
“…The test results led them to propose the utilization of a coefficient to evaluate the influence of pile installation methods on the pile's bearing capacity. He et al [17] compared the load-carrying capacity of bottom-uplift piles and anchor piles in their study, based on load tests on foundation piles. They found that bottom-uplift piles had double the peak load-carrying capacity of conventional uplift piles.…”
Section: Introductionmentioning
confidence: 99%
“…Various foundations are considered depending on the type of construction. Shallow foundations are chosen over deep foundations if the soil carrying capacity is adequate for the weight of the structure 16 , 17 . When the soil carrying capacity is insufficient to support the load of the structure, a deep foundation or a mix of the two is used.…”
Section: Introductionmentioning
confidence: 99%
“…Cairo et al used the boundary element method based on the stiffness matrix method to study the key characteristics of soil-structure interaction (SSI) and effectively evaluated the effects of soil-structure interaction with pile foundations under steady-state conditions [1]. HE et al explored the working mechanism and bearing characteristics of bottom-lift piles through the experimental data of pile-bearing capacity tests of a certain project and numerical simulation methods, and they proposed corresponding design suggestions [2]. LIU Jinbo et al concluded that the settlement deformation of prefabricated extruded piles increases with the decrease of pile spacing through the comparative analysis of the influence of pile spacing on settlement deformation [3].…”
Section: Introductionmentioning
confidence: 99%